2023
DOI: 10.1002/glia.24427
|View full text |Cite
|
Sign up to set email alerts
|

Microglia morphotyping in the adult mouse CNS using hierarchical clustering on principal components reveals regional heterogeneity but no sexual dimorphism

Abstract: Microglia are the resident macrophages of the central nervous system (CNS) and play a pivotal role in immune surveillance and CNS homeostasis. Morphological transitions in microglia are indicative for local changes in the CNS microenvironment and serve as a proxy for the detection of alterations in the CNS, both in health and disease.Current strategies to 'measure' microglia combine advanced morphometrics with clustering approaches to identify and categorize microglia morphologies. However, these studies are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…There has been a concerted effort as a field to move away from dualistic characterization of all microglia as “resting” or “activated,” which is often described in terms of morphological differences, and toward a clearer understanding and appreciation for the heterogeneous “states” of microglia that coexist in the brain in any given context ( Dubbelaar et al, 2018 ; Paolicelli et al, 2022 ). In line with these efforts, there have been many recently published tools that classify and analyze microglia morphological subpopulations in an automated and high-throughput manner ( York et al, 2018 ; Salamanca et al, 2019 ; Clarke et al, 2021 ; Leyh et al, 2021 ; Colombo et al, 2022 ; Melo et al, 2023 ; Reddaway et al, 2023 ; van Weering et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a concerted effort as a field to move away from dualistic characterization of all microglia as “resting” or “activated,” which is often described in terms of morphological differences, and toward a clearer understanding and appreciation for the heterogeneous “states” of microglia that coexist in the brain in any given context ( Dubbelaar et al, 2018 ; Paolicelli et al, 2022 ). In line with these efforts, there have been many recently published tools that classify and analyze microglia morphological subpopulations in an automated and high-throughput manner ( York et al, 2018 ; Salamanca et al, 2019 ; Clarke et al, 2021 ; Leyh et al, 2021 ; Colombo et al, 2022 ; Melo et al, 2023 ; Reddaway et al, 2023 ; van Weering et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Single‐cell images of microglia were selected and processed for morphometric analysis as described previously (van Weering et al., 2023; Zhang et al., 2021). A list of the morphometric parameters with explanations is provided in Supplemental Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Males continue to have a higher density of microglia in the hippocampus and cortex [120]. However, using hierarchical clustering on principal components, a recent study of the microglia of the adult mouse central nervous system found no sex differences in microglial morphology [122]. These discrepancies in microglial density and morphology could arise from a variety of sources, including pathogen exposure in housing, tissue processing and immunostaining techniques, and quantitative approaches.…”
Section: Sexually Dimorphic Microgliamentioning
confidence: 99%
“…Females: more activated in cortex, hippocampus, amygdala [116] Males: more complex branching in prefrontal cortex [117] P60 Rat Females: more activated in cortex, hippocampus, amygdala [116] Mouse Females: more transcriptionally mature [127] Mouse Females: increased inflammatory gene expression [127] 2-6 months Mouse Males: IFN-dependent migration after injury [135] 12 weeks Mouse Males: express more inflammatory genesFemales: more neuroprotective [129] P90 Rat Females: more complex branching in prefrontal cortex [117] 3 months Mouse No difference in morphology in any brain, spinal cord region [122] 13 weeks Mouse Males: higher density in hippocampus, cortex, amygdalaNo difference in density in striatum, cerebellumMales: greater antigen presentation capability [120] 18 months Mouse Females: more phagocytic, reduced ability to respond to insult [137] 22-25 months Mouse Females: express more disease, senescence genes [132] 24 months Mouse Females: express more inflammatory genes [128] * E, embryonic day; and P, postnatal day.…”
Section: Sexually Dimorphic Microgliamentioning
confidence: 99%